(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article analyzes the key factors influencing the improvement of modern business management efficiency using a systematic approach. The study identifies the main determinants of management effectiveness and examines them in terms of human capital, organizational, and strategic dimensions. The theoretical foundations of each factor are clarified, and their role in the management system is scientifically substantiated. The results indicate that the development of human capital, organizational flexibility, and strategic planning play a crucial role in enhancing management efficiency. A conceptual approach for improving management effectiveness is proposed. The findings can serve as a scientific basis for the development of modern management systems.